2021
DOI: 10.33736/bjrst.2879.2021
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Molecular Screening of Potential Ligninolytic Microbes from Termite (Coptotermes curvignathus) Gut

Abstract: Ligninolytic microbes have great potential in converting high lignin by-products to more utilisable products by decomposing the lignin-rich agricultural and industrial wastes. Thus, the aim of this study are to screen and identify the potential ligninolytic microbes from the termite (Coptotermes curvignathus) gut. The study was conducted at Universiti Putra Malaysia Bintulu Sarawak Campus, Malaysia. Twenty-seven microbes isolated from termite gut obtained from the Microbiology Laboratory, Faculty of Agricultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…But Hameed et al [53] suggested that combining conventional and molecular techniques can help achieve the accuracy, rapidness, and reliability of microbiome results. Hence, the technique also been proven in a few groups of wildlife studies throughout Southeast Asia [23,29,33,51,54,55].…”
Section: Methodological Variability In Gut Microbiome Studies In Sout...mentioning
confidence: 99%
See 1 more Smart Citation
“…But Hameed et al [53] suggested that combining conventional and molecular techniques can help achieve the accuracy, rapidness, and reliability of microbiome results. Hence, the technique also been proven in a few groups of wildlife studies throughout Southeast Asia [23,29,33,51,54,55].…”
Section: Methodological Variability In Gut Microbiome Studies In Sout...mentioning
confidence: 99%
“…Minard et al [20], Surat et al [21], and Rosso et al [22]) and honeybees (eg. Lombogia et al [23], Duong et al [24], Gruneck et al [25], and Lanh et al [26]), there are also a study on fleas by Rombot et al [27] Badrulisham et al [28], termites by Simol et al [29], cockroach by Ni'matuzahroh et al [30] and weevil by Farah-Nadia et al [31]. Following closely, mammals are a prominent focus with 19 studies.…”
Section: Summary Of Microbiome Studies In Southeast Asiamentioning
confidence: 99%
“…21 Microbes found in the insect gut, including Pseudomonas, Bacillus, Enterobacter, and Paenibacillus, are known to produce lignocellulosic enzymes. 22 Complex interactions exist between gut microbes and their insect hosts to the benefit of both parties. 8 Cellulolytic bacterial isolates were previously reported in the gut of the grasshoppers Oxya chinensis and Oxya velox.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous screening of 27 termite (Coptotermes curvignathus) gut isolates obtained from the collection of the Microbiology Laboratory, Faculty of Agricultural Science and Forestry, Universiti Putra Malaysia Bintulu Sarawak Campus (UPMKB), Malaysia detected only 3 isolates with ligninolytic activity, based on 4 different ligninolytic indicator dyes [16]. The 16S rRNA gene sequencing of these isolates identified them as Bacillus toyonensis, Bacillus cereus, and Bacillus thuringiensis as indicated in Table S1.…”
Section: Introductionmentioning
confidence: 99%